PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAM GAMES TOURNAMENT (OCTOPUS GAMES) DENGAN BANTUAN MEDIA GOOGLE LENS UNTUK MENINGKATKAN HASIL BELAJAR MATERI KLASIFIKASI MAKHLUK HIDUP - Lyca Rahmawati Wakhidah; Yusuf Hanafi; Ferdi Dwi Sagitha; Lyca Rahmawati Wakhidah; Yusuf Hanafi (Universitas Negeri Malang, 2024)
Education is one of the subjects that becomes an urgency in the progress of a nation, education cannot be separated from the teaching and learning process in the classroom which certainly faces problems in achieving the expected goals. One of the problems faced by a teacher is the learning outcomes of students who tend to be low because learning activities are less interesting and involve all students. This study aims to determine the learning outcomes of students after applying the Cooperative Learning learning model of Team Games Tournament (Octopus Games) Type with the Help of Google Lens Media on the classification of living things. This type of research is pre-experiments. Data collection techniques with tests and observations. The learning outcomes of students in the classification of living things have increased by 47% based on the value of the pretest and posttest results. Based on these results, the application of the Team Games Tournament (Octopus Games) Type Cooperative Learning learning model with the help of Google Lens Media can improve student learning outcomes on living things classification material.